Ranger's Apprentice: The Battle for Skandia - Book 4 - Flanagan, John (John Anthony) (New York : Philomel Books, 2008)
After Ranger's apprentice Will battles Temujai warriors to rescue Evanlyn, Will's kingdom of Skandia joins forces with rival kingdom Araluen to defeat a common enemy.
aOriginally published: Oakleaf bearers. Milsons Point, N.S.W. : Random House Australia, 2006.
Keywords: Heroes and heroines -- Fiction; War -- Fiction; Fiction